PENGARUH UTANG LUAR NEGERI, INFLASI, SUKU BUNGA DAN CADANGAN DEVISA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Musthafa, Ade Marwan; Ratna, Ratna (Jurnal Ekonomi Regional Unimal, 2024)
This research aims to analyze the influence of foreign debt, inflation, interest rates and foreign exchange reserves on economic growth in Indonesia. The data used in this research is secondary data obtained from the Central Statistics Agency (BPS) during the 1990-2022 time period totaling 33 data. The data analysis method in this research uses the ARDL model. The research results show that in the short term foreign debt in the current year has no influence on economic growth, however in the previous one year period and the previous two year period foreign debt had a positive and significant influence on economic growth. Meanwhile, in the long term, it shows that foreign debt has a negative and significant effect on economic growth. In the short term, inflation in the current year has a negative and significant influence on economic growth, however, in the previous one year period and the previous two year period, inflation has a positive and significant influence on economic growth. Meanwhile, in the long term, it shows that inflation has a negative and significant effect on economic growth. In the long term, interest rates have a positive and significant effect on economic growth. In the short term, foreign exchange reserves in the current year, the previous one year, two years and three years have a negative and significant influence on economic growth. Meanwhile, in the long term, it shows that foreign exchange reserves have a positive and significant effect on economic growth.